Comparison of the PROMIS and iHOT-12 in Determining Satisfaction Levels After Hip Arthroscopy for FAIS. Issue 5 (May 2023) - Martin, RobRoy L.; Harris, Joshua D.; Ellis, Thomas; Kollmorgen, Robert
Background: The Patient-Reported Outcomes Measurement Information System (PROMIS) has not been fully evaluated for outcomes assessment after hip arthroscopy to correct femoroacetabular impingement syndrome (FAIS). Purpose/Hypothesis: The purpose of this study was to compare the accuracy of the PROMIS Physical Function (PF) and Pain Interference (PI) subscales with the 12-Item International Hip Outcome Tool (iHOT-12) to define patients with 3 unique substantial clinical benefit (SCB) scores—patients who reported ≥80%, ≥90%, and 100% satisfaction at 1 year after hip arthroscopy for FAIS. We hypothesized that the iHOT-12 would be more accurate than the PROMIS-PF and PROMIS-PI subscales in identifying these 3 patient groups. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: We reviewed the records of patients who underwent hip arthroscopy for symptomatic FAIS at 3 centers from January 2019 through June 2021 and had 1-year clinical and radiographic follow-up data. Patients completed the iHOT-12, PROMIS-PF, and PROMIS-PI on initial assessment and at 1 year (±30 days) postoperatively. Postoperative satisfaction was reported on an 11-category scale with anchors defined as "0% satisfied" and "100% satisfied." Receiver operator characteristic analysis was performed to determine the absolute SCB values for the iHOT-12 and PROMIS subscales that would most accurately identify those patients who reported ≥80%, ≥90%, and 100% satisfaction. Area under the curve (AUC) values and 95% CIs for the 3 instruments were compared. Results: Included were 163 patients (111 [68%] women and 52 [32%] men), with a mean age of 26.1 years. Corresponding absolute SCB scores for patients who reported ≥80%, ≥90%, and 100% satisfaction were as follows: iHOT-12, 68.4, 72.1, 74.7; PROMIS-PF, 45, 47.7, 49.9; and PROMIS-PI, 55.9, 52.4, 51.9. The AUC ranged between 0.67 and 0.82, with overlapping 95% CIs indicating a minimal difference in accuracy between the 3 instruments. Sensitivity and specificity values ranged between 0.61 and 0.82. Conclusion: The PROMIS-PF and PROMIS-PI subscales were as accurate as the iHOT-12 in defining absolute SCB scores for patients reporting ≥80%, ≥90%, and 100% satisfaction at 1-year follow-up after hip arthroscopy for FAIS.